KEGIATAN PAGELARAN SENI DI SMP NEGERI 5 LHOKSEUMAWE - Julia Julia; Sri Aryati (Cross-border, 2021)
This study entitled "Art Performance Activities at SMP Negeri 5 Lhokseumawe, raised the problem of how the implementation of performing arts activities at SMP Negeri 5 Lhokseumawe. This study aims to describe the implementation of performing arts activities at SMP Negeri 5 Lhoseumawe, and the obstacles faced during the implementation of the activity. The approach used is a qualitative approach, while the type of research used is descriptive.The sources of research data are trainers/supervisors and students who take part in performing arts activities at SMP Negeri 5 Lhokseumawe.The data collection techniques used are observation, interviews and documentation.Analysis techniques data, namely data reduction, data presentation and data verification.The results of research on the implementation of performing arts activities at SMP Negeri 5 Lhokseumawe are held annually in the even semester with learning guidance of 4 face-to-face meetings in class, Even before entering the exhibition material, the teacher s eni has conveyed information about what things will be planned at the exhibition. The rest of the guidance activities are carried out outside of class hours, both scheduled and free, but still under the coordination of the art teacher and homeroom teacher. The implementation of performing arts activities at SMP Negeri 5 Lhokseumawe is in accordance with the curriculum and syllabus set by the Ministry of National Education that this art performance is one of the places to develop students' talents and interests and potential in the arts. This activity really helps students in exploring their artistic soul. The obstacles faced were the narrowness of the field where the event took place so that the installation of tents and performances as well as a place for exhibition stands and bazaars was a little less than perfect, besides the lack of concern for a small number of homeroom teachers in assisting in guiding their students, then students were less disciplined in carrying out the directions given by the supervisor, the lack of support from the guardians of students in allowing their sons and daughters to carry out training activities, especially in the branch of music and dance performances, is due to the long time required for these exercises.